2012
DOI: 10.1105/tpc.110.081885
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis E3 Ubiquitin Ligase HOS1 Negatively Regulates CONSTANS Abundance in the Photoperiodic Control of Flowering

Abstract: The Arabidopsis thaliana early in short days6 (esd6) mutant was isolated in a screen for mutations that accelerate flowering time. Among other developmental alterations, esd6 displays early flowering in both long-and short-day conditions. Fine mapping of the mutation showed that the esd6 phenotype is caused by a lesion in the HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES1 (HOS1) locus, which encodes a RING finger-containing E3 ubiquitin ligase. The esd6/hos1 mutation causes decreased FLOWERING LOCUS C expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
268
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(284 citation statements)
references
References 86 publications
15
268
0
1
Order By: Relevance
“…In addition to COP1 and FKF1 that were discussed above, HOS1 and TOE1 have also been implicated in regulating CO stability (Lazaro et al , 2012; Zhang et al , 2015). Although it is possible that HOS1 and TOE1 might also be regulated by PRRs, our genetic data with the cop1 toc1 prr5 prr7 prr9 quintuple mutant do not currently support this hypothesis, because the cop1 mutation is epistatic to the prr mutations with respect to CO protein abundance (Fig 4E and F).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to COP1 and FKF1 that were discussed above, HOS1 and TOE1 have also been implicated in regulating CO stability (Lazaro et al , 2012; Zhang et al , 2015). Although it is possible that HOS1 and TOE1 might also be regulated by PRRs, our genetic data with the cop1 toc1 prr5 prr7 prr9 quintuple mutant do not currently support this hypothesis, because the cop1 mutation is epistatic to the prr mutations with respect to CO protein abundance (Fig 4E and F).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, PHYTOCHROME-DEPENDENT LATE FLOWERING (PHL) interacts with both phyB and CO, and prevents phyB-mediated degradation of CO (Endo et al, 2013). HOS1, a ring domain-containing E3 ligase destabilizes during the day (Lazaro et al, 2012). ZTL and LKP2 promote degradation of CO in the morning, whereas FKF1 stabilizes CO by direct interaction (Song et al, 2014(Song et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, HOS1 negatively regulates auxin biosynthesis in the control of hypocotyl elongation. 27 It has been previously reported that hos1 mutants show reduced leaf area, 28 although underlying molecular mechanism is elusive. Thus, we wanted to know how HOS1 regulates leaf expansion.…”
mentioning
confidence: 99%